Going Online for Social Change: Techniques, barriers and possibilities for community groups. - SALTER, COLIN (Social Alternatives)
The article discusses the use of the internet by community groups to achieve their aims. It is noted that open source technologies are designed to be collaborative and decentralized. The online techniques used by the Sandon Point Community Picket are cited as an example of how a grassroots activist group can promote its message to a larger audience. The benefits of using social media to promote social change are discussed, along with some of the challenges and technical considerations that are involved.